A multicentre study of naevus‐associated melanoma vs. de novo melanoma, tumour thickness and body site differences. (1st April 2021) - Dessinioti, C.; Geller, A.C.; Stergiopoulou, A.; Dimou, N.; Lo, S.; Keim, U.; Gershenwald, J.E.; Haydu, L.E.; Dummer, R.; Mangana, J.; Hauschild, A.; Egberts, F.; et al.
Summary: Background: Whether melanoma in histological contiguity with a naevus [naevus‐associated melanoma (NAM)] is distinctly different from melanoma arising de novo remains unclear. Objectives: To determine whether the characteristics of de novo melanoma differ from NAM and are not due to naevus obliteration in thicker tumours. Methods: We conducted a multicentre retrospective study of de novo melanoma and NAM in seven referral centres in Europe, Australia and the USA between 2006 and 2015. Results: In a total of 9474 localized melanomas, de novo melanoma was associated with thicker tumours and body site differences compared with NAM. In the subset of T1 melanomas ( n = 5307), similar body site differences were found in multivariate analysis by body site. When compared with NAM, de novo melanoma was more likely to affect older individuals (≥ 70 years) when located on the head/neck [odds ratio (OR) 4·65, 95% confidence interval (CI) 2·55–8·46], the trunk (OR 1·82, 95% CI 1·40–2·36) or the upper extremity (OR 1·69, 95% CI 1·14–2·50), was more likely to affect female patients when located on the lower extremities (OR 1·36, 95% CI 1·03–1·80), and was more likely to be of the nodular melanoma subtype (OR 2·23, 95% CI 1·14–4·35) when located on the trunk. De novo melanoma was less likely to have regression present compared with NAM. Conclusions: Clinicopathological and body site differences between de novo melanoma and NAM support the divergent pathway model of development. These differences were also found in thin melanomas, suggesting that de novo melanomas are different from NAM and their differences are not due to the obliteration of naevus remnants in thicker tumours. Abstract : What is already known about this topic? Cutaneous melanoma appears de novo in approximately 70% of cases and has adjacent naevus remnants on histological examination [naevus‐associated melanoma (NAM)] in the remaining 30% of cases. Whether melanoma arising de novo is a biological type distinct from NAM remains unclear. Robust conclusions on the differences between de novo melanoma and NAM have been hindered by the possible obliteration of naevus in thicker melanomas. What does this study add? In 9474 patients with localized melanoma there were body site differences for de novo melanoma compared with NAM, supporting the divergent pathway model of melanoma development. In 5307 T1 melanomas there were similar body site associations for de novo melanoma and older age at diagnosis, female sex, the nodular subtype and absence of regression. These findings suggest that de novo melanomas are different from NAM and the differences are not due to the obliteration of naevus remnants in thicker tumours. Linked Comment: J. Wiggins and D. Polsky. Br J Dermatol 2021; 185 :9–10 .